Physicians' and nurses' thoughts and concerns about introducing neonatal male circumcision in Thailand: A qualitative study - Kriengkrai Srithanaviboonchai (2018)
© 2018 The Author(s). Background: Neonatal male circumcision (NMC) is an alternative approach to adult male circumcision for HIV prevention. Recent studies found that NMC was rarely performed in Thailand and that most Thai health professionals did not recognize that NMC could reduce the risk of HIV infection and would not want NMC services in their hospitals. This study explored the thoughts and concerns of Thai government health staff regarding the introduction of NMC in government health facilities as a public health measure. Methods: In-depth interviews with physicians, nurses and physician administrators from four different levels of government hospitals in four provinces representing 4 regions of Thailand were conducted after provision of education regarding the benefits and risks of NMC. Interviews were audio recorded and analyzed using Atlas.ti software to develop themes. Results: Six themes emerged from the data of 42 respondents: understanding of the benefits of NMC; risks of NMC; need for a pilot project; need for staff training and hospital readiness; need for parental/family education; and need for public awareness educational campaign. Major concerns included possible medical complications of NMC, infringement of child rights, and lack of understanding from staff and parents. The respondents emphasized the need for a clear policy, proper training of staff, financial and equipment support, and piloting NMC rollout before this measure could be fully implemented. Conclusions: Thai health professionals who took part in this study expressed several concerns if NMC had to be performed in their health care facilities. There is significant preparation that needs to be done before NMC can be introduced in the country.